2001
DOI: 10.1051/0004-6361:20011097
|View full text |Cite
|
Sign up to set email alerts
|

Buried magnetic flux tubes in giant stars near the "Coronal Dividing Line"

Abstract: Abstract. We apply the "solar paradigm" for stellar magnetic activity to the post-main-sequence evolution of stars in the mass range 1 M ≤ M ≤ 3 M . The model starts from a strong toroidal magnetic field generated by a dynamo working in the overshoot layer below the convection envelope. Once a critical field strength is exceeded, an undulatory (Parker-type) instability leads to rising flux loops. Upon emergence at the stellar surface, they form bipolar magnetic regions and large-scale coronal loops. By conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…To facilitate some level of comparison between these initial condition assumptions, we also perform some simulations where flux tubes initially in MEQ rise through a quiescent convection zone. Similar to TFT models in stars with small radiative cores (e.g., Granzer et al 2000;Holzwarth & Schüssler 2001), we find that most of these flux tubes slip poleward, driven by a magnetic tension force that is dominant compared to buoyancy. However, strongly super-equipartition flux tubes can develop low-order ( = m 1 2 -) unstable modes if the magnetic field strength and radius of curvature arelarge enough.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…To facilitate some level of comparison between these initial condition assumptions, we also perform some simulations where flux tubes initially in MEQ rise through a quiescent convection zone. Similar to TFT models in stars with small radiative cores (e.g., Granzer et al 2000;Holzwarth & Schüssler 2001), we find that most of these flux tubes slip poleward, driven by a magnetic tension force that is dominant compared to buoyancy. However, strongly super-equipartition flux tubes can develop low-order ( = m 1 2 -) unstable modes if the magnetic field strength and radius of curvature arelarge enough.…”
Section: Discussionsupporting
confidence: 74%
“…Traditional TFT models tend to assume that the dynamo mechanism generates toroidal flux tubes at the interface between the radiative interior and the convection zone, often assumed to be in mechanical force equilibrium (MEQ) and neutral buoyancy (e.g., Caligari et al 1995;Granzer et al 2000;Holzwarth & Schüssler 2001;Weber et al 2011). However, recent simulations of global-scale dynamo action in spherical shells (e.g., Nelson et al 2014) have demonstrated that, at least in some parameter regimes, buoyant magnetic loops can be built by a distributed dynamo without a tachocline region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition in topology is ascribed to a change in the origin of the field: as the stellar rotation drops below a critical value, the spin-catalyzed dynamo gives way to a field generation mechanism requiring fluid turbulence as found in the convection zone. It has also been suggested that the magnetic flux tubes that rise up from underneath the convection zone to the stellar surface where they form large scale coronal loops, become trapped in the convective envelope as the convection zone deepens to the right of the DLs (Holzwarth & Schüssler 2001). However, Ayres et al (1997Ayres et al ( , 2003 have found evidence in "non-coronal" giants that coronal loops can still rise to the stellar surface: the loops extend beyond the cold molecular layer just above the stellar photosphere, but are at least partially submerged in the chromosphere/COmosphere, where the coronal X-rays are attenuated by overlying material.…”
Section: Coronal Transition Region and Wind Dividing Linesmentioning
confidence: 99%
“…If the convection zone extends to at least 80% of the stellar radius (Holzwarth & Schüssler 2001), magnetic flux loops are trapped there, because magnetic stresses at the tips of the loops act against convective buoyancy. This also explains the weakness of the coronal X-ray luminosity, and why the magnetic fluctuations are rare.…”
Section: Coronal Loopsmentioning
confidence: 99%